Penerapan Permainan What’s In Here Berbasis Model TGT untuk Menumbuhkan Kemampuan Berpikir Kritis Siswa - Susilo, Novika Hapsari; Wijayanti, Arfilia; Artharina, Filia Prima (Jurnal Ilmiah Sekolah Dasar, 2019)
This study aims to determine the application of What 's In Here game based on the Team Games Tournament (TGT) model to foster critical thinking skills of fourth grade students at Gabus 04 SDN Pati. This research is quantitative research. This study uses One Group Pretest-Posttest Design. The population in this study were all fourth grade students at Gabus 04 Pati SDN totaling 31 students in the 2018/2019 school year. The instruments used are (1) Test. (2) Questionnaire, (3) Observation, and (3) Documentation. Data analysis using technical analysis of normality test data, hypothesis testing (t-test), and N-Gain Test. The normality test is used to find out whether the class is normally distributed or not. Hypothesis testing uses the t-test. The N- Gain test is used to calculate students' critical thinking abilities. The results of the research conducted can be concluded that the game What 's In Here can be applied to foster critical thinking skills of fourth grade students at Gabus SDN 04 Pati. This can be seen from the improvement of students' critical thinking skills. Besides that it is reinforced by the results of t-test calculations obtained by tcount for critical thinking skills of 7.232 and ttable of 1.694 because of tcount (7.232)> ttable (1.694), so this shows that the t test of critical thinking skills is significant. While the results of the observations carried out the highest aspects, namely the synthesizing skills of 78.2%.